Consuming religion : Christian faith and practice in a consumer culture - Miller, Vincent Jude (2004)
Terrence W. Tilley, University of Dayton
How to think about consumer culture -- The commodification of culture -- Consumer religion -- Desire and the Kingdom of God -- The politics of consumption -- Popular religion in consumer culture -- Stewarding religious traditions in consumer culture
Includes bibliographical references (pages 229-250) and index
Keywords: Consumption (Economics) -- Religious aspects -- Christianity; Christianity and culture